‘Undergoing' as posthuman literacy research in an in/formal settlement primary school in South Africa - Crowther, Judith Lynne (School of Education, 2022)
My research began with a critical incident of my teaching performance being monitored in a British primary school classroom. A dis/continuous re-turning to the incident catalyses analysis of concepts in education and the educator's role in teaching literacy. Analysis is predominantly enabled through the critical theories and philosophies of Tim Ingold, Rosi Braidotti and Karen Barad. Eight years later, having moved back to South Africa, my research continued in an in/formal settlement government school where I was employed as a literacy support teacher. Inspired by Murris and Haynes' Philosophy with Picturebooks approach, I conducted philosophical enquiries with small groups of primary school children (aged 9-12) as a way of doing literacy support. The children were diagnosed by the school as having barriers to learning and were research participants for a period of six months. Created data includes critical incidents, fieldnotes, children's workbooks, photographs and vignettes of small group enquiries. Central in my research is the notion of subjectivity in an educational community. The formation of subjectivity in community aligns with Ingold's notion of ‘undergoing' which is a guiding concept throughout. I put forward the thesis that ‘undergoing' offers an important alternative to dominant views of education. ‘Undergoing' refers to what we (on a planetary scale) are becoming, that continuously (re)shapes and (re)orients pre-arranged educational ‘doings'. Research as ‘undergoing' is not about producing knowledge to fill in gaps on a given (transcendently known) plane. ‘Undergoing' troubles such humanist literacy support approaches that focus only on language and are guided by notions such as ‘back to basics' or ‘simple to complex'. The concept of ‘undergoing' works to show how literacy education involves processes of subjectification where relational entanglements precede entities formed. In the thesis I argue how critical posthumanism and, in particular, the concept ‘undergoing' enables affirmative posthuman literacy research and pedagogy. ‘Undergoing' matters ethically and politically, because it renders capable so-called ‘failing' children in literacy pursuits, in a context of poverty. It also renders capable so-called ‘failing' teachers in their pedagogical endeavours.